Challenges To Toyota Caused By Recall Problems, Social Networks And Digitisation - Rajasekera, Jay (Asian Academy of Management (AAM), 2013)
The recent recall problems that shook Toyota raised questions about the company's openness with the public. Media attention and the intervention by governments in Toyota's largest markets in North America, Europe, China, and Japan kept Toyota's management in the spotlight. The crisis also exposed the power of social media. Although authoritarian regimes can control social media, public companies cannot. They have to live with it by either countering effectively when a crisis begins to brew or suffering the consequences when it grows out of proportion. If Toyota manages social media strategically, can it overcome the recall debacle and protect the reputation it has built over decades as the top-quality automaker in the world? What challenges does the increasingly digitalised auto industry present to Toyota? These are the main subjects of this paper.